Controlled hyperventilation using a new ventilation navigator software: a feasibility study to provoke hypocapnia and respiratory alkalosis - Kardos, Attila; Yong, Qi; Kardos, Barbara; Garces, Nerea Sanfeliu; Burgess, Ellie; Chan, Kenneth; Makris, Nikolaos (Oxford University Press (OUP), 2026)
Aims: To develop a ventilation navigator to provide controlled hyperventilation and to assess the feasibility to monitor hypocapnia and respiratory alkalosis in healthy subjects. Methods and results: We developed the Ventilation Navigator software using C++ and utilizing high-precision timers as an advanced platform for respiratory guidance and control, incorporating adjustable breathing rate, and tidal volume, a session timer for automatic cessation. Its graphical user interface is designed to deliver clear visual cues to the patient, facilitating controlled breathing. We assessed the utility of controlled hyperventilation in five healthy probands using end-tidal CO2 (ETCO2) against capillary CO2 and pH. We have successfully achieved respiratory alkalosis (pH >7.50) between 70% and 90% of the subjects’ baseline ETCO2. The linear mixed-effects modelling demonstrated a significant association between ETCO2 and capillary pH (β = −0.063, SE = 0.008, P < 0.001). There was a moderate, clinically relevant agreement between capillary and ETCO2 with an offset of 0.48 (1.50 – (−0.54)); however, ETCO2 was significantly associated with capillary CO2 (β = 0737, SE = 0.115, P < 0.001) after accounting for repeated measures within individuals. A strong within-individual associations for ETCO2 vs. capillary CO2 as demonstrated (Rrm = 0.857, 95% confidence interval: 0.628–0.949, P < 0.001). Conclusion: We developed a ventilation navigator application to deliver a controlled hyperventilation and assess its feasibility to monitor hypocapnia and respiratory alkalosis in healthy subjects. We are proposing this controlled physiological test to be implemented in the routine diagnostic workup to investigate coronary vasoreactivity in patients having angina with non-occlusive coronary artery disease after it has been validated in patients.
Keywords: 3208 Medical Physiology; 32 Biomedical and Clinical Sciences; Heart Disease - Coronary Heart Disease; Heart Disease; Cardiovascular; Bioengineering; Lung; Clinical Research; ventilation navigator; hyperventilation test; vasoreactivity; ANOCA